Analysis of Participants in the Second Major Division of Numbers - Jin, Gyusang (HIPHIL Novum, 2022)
While many scholars demarcated the text of Numbers using rhetorical criteria such as theme or plot, this study discovered the syntactic-hierarchical structure of Numbers and found the demarcations by Elaborate Divine Speech Formulae. I used the text-linguistics of Eep Talstra and the linguistic inventory of ETCBC (Eep Talstra Center for Bible and Computer). The text-hierarchical structure resulted in two major divisions, Num 1–8 and 9–36, and also six embedded sections, 1:1–3:13, 3:14–8:26, 9:1–20:22, 20:23–33:49, 33:50–34:29, and 35:1–36:13, within them. First, the analysis of participants verifies the validity of the demarcations displaying weak connectivity in terms of shared participants, and strong separability in terms of unique participants. Second, the analysis of participants elaborates well on the discourse function of each of the two major divisions and the six sections. In this paper, I focus on the second major division.